New species and new occurrences of Copidognathus (Acari, Halacaridae) from the northern littoral zone of São Paulo State (Brazil) - Pepato, Almir R.; Tiago, Cláudio G. (Zootaxa, 2005)
Seven species from the northern littoral zone of São Paulo State (Brazil) are here reported. Copidognathus tupinamborum sp. nov., C. sophiae sp. nov., C. tamoiorum sp. nov. and C. ditadii sp. nov. are described. C. modestus Bartsch, 1984, C. longispinus Bartsch & Iliffe, 1985 and C. floridensis (Newell, 1947) are obtained from the Brazilian littoral for the first time and their descriptions are extended with descriptions of their protonymphs.